The (dis)-engendering of violence: towards an eschatological understanding of being male and female - Makant, Mindy (Theology today, 2016)
Violence against women is a theological problem. The history of interpretation of the narratives of creation and fall, and thus the development of Christian theology, has often assumed a hierarchical ordering of gendered relations which has (inadvertently?) justified male violence against women. This article offers a theological interpretation of gender based on the eschatological promises of salvation rather than the narratives of creation and fall, an interpretation rooted in relatedness in which violence can only be interpreted as sin.